2014
DOI: 10.1161/circresaha.114.302221
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Type I Interferon in Pulmonary Arterial Hypertension

Abstract: P ulmonary arterial hypertension (PAH) is a rare but devastating disease, which is defined as a mean pulmonary artery pressure of ≥25 mm Hg with a normal pulmonary capillary wedge pressure. It is characterized by remodeling of the muscular, precapillary vessels, leading to an increase in pulmonary vascular resistance. The associated strain exerted on the right heart ultimately results in right heart failure and premature death. 1,2 Autoimmunity has long been implicated in PAH 3 and, most recently, evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
132
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 48 publications
2
132
0
2
Order By: Relevance
“…More recently, it has been demonstrated that type I IFN receptor knockout (IFNAR1(-/-)) mice were protected from the effects of hypoxia on the right heart, vascular remodelling, and raised serum ET-1 levels. These data suggested that type I IFN could mediate PAH via an action of IFNAR1 [15]. Further studies are needed to establish the effect of IFN on other animal models of PH, such as PH induced by monocrotaline or chronic hypoxia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, it has been demonstrated that type I IFN receptor knockout (IFNAR1(-/-)) mice were protected from the effects of hypoxia on the right heart, vascular remodelling, and raised serum ET-1 levels. These data suggested that type I IFN could mediate PAH via an action of IFNAR1 [15]. Further studies are needed to establish the effect of IFN on other animal models of PH, such as PH induced by monocrotaline or chronic hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by the publication of several isolated case reports [7][8][9][10][11][12][13][14] and by experimental studies [15][16][17][18]. IFNs have powerful actions within the immune system where they play key anti-viral, anti-bacterial and anti-tumoural roles.…”
Section: Introductionmentioning
confidence: 94%
“…Interferon has been linked to an increased level of Endothelin-1 which is an important modulator in the pathogenesis of PH [58]. Pulmonary hypertension diagnosis may be delayed long, up to 3 years, after initiation of interferon treatment.…”
Section: Interferon Amentioning
confidence: 99%
“…Hypertension (p 677) 12 Interferon prompts the development of pulmonary arterial hypertension in mice, report George et al…”
Section: Interferon and Pulmonary Arterialmentioning
confidence: 99%